The Expression of Moral Values in Children Aged 5-7 in Terms of Emotions - Jasiūnaitė, Placida (Jaunųjų mokslininkų darbai, 2016)
In the light of ever spreading secularism and neoliberalism in the modern global world traditional values (including personal moral values) are undergoing rapid transformation thus the paper addresses the issue of the development of moral values at pre-school age. Assuming that childhood marks the start of the moral and social-emotional development of an individual, the paper seeks to stress early internalisation of fundamental moral values of children aged 5-7. Since children at this age mostly demonstrate internalisation of moral values at behavioural and emotional level, the paper sought to examine the expression of moral values of children aged 5-7 in terms of emotional experiences. Drawing on empirical data collected from parents and pre-school education teachers the author revealed the emotional experiences characteristic of this age group children, and their link with moral values. Some differences in emotional experiences that depend on the child’s gender, place of residence and type of a pre-chool institution were also highlighted and compared with some findings of foreign authors.
Keywords: children 5 to 7 years old; parents; teachers; moral values; emotional experiences